The complete chloroplast genome of Catalpa speciosa (Warder) Engelmann (Bignoniaceae) - Qing-guo Ma; Jian-guo Zhang; Jun-pei Zhang (Mitochondrial DNA. Part B. Resources, 2020)
Catalpa speciosa (Warder) Engelm. is a precious Catalpa tree widely used as a large ornamental shade tree. In this study, the complete chloroplast genome was assembled from Illumina sequencing data. The completed plastome was 158,239 bp in length, including a large single copy (LSC) region of 85,036 bp, a small single copy (SSC) region of 12,639 bp, and a pair of inverted repeat (IR) regions of 30,282 bp. The overall GC content of the genome was 38.09%, and the corresponding values of the LSC, SSC and IR regions were 36.44%, 33.57%, and 41.35%, respectively. A total of 129 genes were annotated, including 83 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Phylogenetic analysis was carried out based on complete plastome sequences of C. speciose and 11 other species from Bignoniaceae family. The newly characterized complete chloroplast genome will provide essential data for further studies of C. speciosa.